Os sentidos da escolarização para os jovens concluintes do ensino médio de uma pequena cidade do sul do estado de Goiás - Pinheiro, Rafael Gomes (2017)
Inserted in the line of research Principles on Educational Processes, this study has as its theme the relationship between young people and schooling processes. Researchers have pointed out the need to carry out studies with young people from towns, since, from the urban perspective of large cities, these subjects are different from those that live far from these centers. It is argued that the emphasis of the research on the lives of urban youth can compromise the understanding of the totality of young Brazilians. The purpose of this study was to apprehend the meanings of schooling for the young high school graduates of a town in the countryside of the state of Goiás. It is assumed that historical, social and economic conditions, among others, may interfere in the senses attributed to the youth and their relationship with social groups, such as the school. For that purpose, the research developed had an empirical qualitative approach, using the procedures of observation, questionnaire and text production alongside thirty-three young students of the third year of Colégio Estadual Bernardino Guimarães, a public high school and the only in the town of Água Limpa (GO). The high school has been permeated by policies, programs and projects, that below to its promises to improve the quality of education, meet the requirements of international organizations, guided by principles that have as a consequence the direct link of the school to the world of work and, as a main objective, the performance of young students in large-scale evaluation systems. The life context of the young students was considered to be rurban, considering the characteristics of the locality. The town limits, however, did not appear as a barrier for these young people to build future expectations beyond their town, especially because they are connected to diverse communicative media. It was observed that the meanings attributed by young people to schooling were related, in particular: i) to the school as a space of sociability; (ii) to the difficulties faced by young people in completing basic education; and iii) to the valuation of the school as a possibility of upward mobility.